Antifungal Activities of Some Pleurotus Species (Higher Basidiomycetes) - OWAID, Mustafa Nadhim; AL SAEEDI, Sajid Salahuddin Saleem; ABED, Idham Ali; SHAHBAZI, Pedram; SABARATNAM, Vikineswary (Walailak Journal of Science and Technology (WJST), 2016)
This study investigated the antifungal activities of 4 Pleurotus spp. (oyster mushrooms) against 3 pathogenic fungi: Trichoderma harzianum, Verticillium sp., and Pythium sp. The antifungal activity of the mycelia of oyster mushrooms was tested against 3 pathogenic fungi grown in fresh PDA medium using dual culture testing. The antifungal activities of the culture filtrates of oyster mushrooms were tested in solid and liquid media. The highest inhibition activity, of 55.56 %, was observed with P. salmoneostramineus against Verticillium sp., while the least percent inhibition of 46.15 % was with the mycelia of Pleurotus ostreatus against T. harzianum. Then, Pleurotus ostreatus grew over the mycelia of Pythium sp. in 5.33 days, while P. cornucopiae var. citrinopileatus mycelia did not grow over the mycelia of Verticillium sp. and T. harzianum. Antifungal activity of the culture filtrate of Pleurotus spp. on agar media was variable. The highest inhibition was 12.33 %, followed 11.60 % for P. salmoneostramineus and P. ostreatus against Verticillium sp. and T. harzianum, respectively, whereas lower inhibitions at 1.34 and 1.75 % were observed for the culture filtrates of P. cornucopiae and P. ostreatus against Verticillium sp. and Pythium sp., respectively. In liquid media, the highest inhibition was 55 and 50 % with P. ostreatus and P. salmoneostramineus culture filtrates against T. harzianum and Verticillium sp., respectively, whereas the lowest inhibition was 3.33 % in the case of P. ostreatus against T. harzianum.